Coupled Coincidence Point Results for (ψ,α,β)-Weak Contractions in Partially Ordered Metric Spaces - A. Razani; V. Parvaneh (Journal of Applied Mathematics)
In this paper coupled coincidence points of mappings satisfying a nonlinear contractive condition in the framework of partially ordered metric spaces are obtained. Our results extend the results of Harjani et al. (2011). Moreover, an example of the main result is given. Finally, some coupled coincidence point results for mappings satisfying some contraction conditions of integral type in partially ordered complete metric spaces are deduced.